Insights on photophysical proprieties of DCM dye in PVK host matrix. Issue 9 (2nd May 2013) - Bruno, Annalisa; Mauro, Anna De Girolamo Del; Nenna, Giuseppe; Haque, S.A.; Minarini, Carla
<x xml:space="preserve">Abstract</x> In this work, the photophysical proprieties of 4‐(dicyanomethylene)‐2‐methyl‐6‐(p‐dimethylaminostyryl)‐4H‐pyran (DCM) dye in the poly‐vinylcarbazole (PVK) matrix are analyzed with a particular attention to the energy transfer processes between the matrix and the dye. PVK films doped with weight percent varying from 1 to 8 wt% of DCM have been fabricated. The emission spectra are dominated by the presence of DCM and a strong red shift in the emission spectra of the blend has been observed as function of dye concentration. A quenching effect in the excitons lifetime increasing the concentration of the dopants has been observed. These two phenomena have been studied in terms of energy processes inside the blends. POLYM. COMPOS., 34:1500–1505, 2013. © 2013 Society of Plastics Engineers